MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION DAN TALKING STICK UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIKA SISWA SMP - Yuni Arta Rahmawati; Nora Susilowaty (Jurnal Padegogik, 2021)
Mathematical reasoning is one of the important abilities in mathematical learning. This study aims to determine whether there are differences in increasing mathematical reasoning abilities of junior high school students who obtain the Student Teams Achievement Division and students who receive the Talking Stick. This research was conducted on students in class VII-I obtained the Student Teams Achievement Division learning model while students in class VII-J obtained the Talking Stick learning model. The research sample consisted of 36 students of class VII-I and 36 students in class VII-J. The instrument used in this study was a test of mathematical reasoning ability on the subject of Social Arithmetic. Based on the results of the study concluded that: 1) Mathematical reasoning ability of students in the class who obtained the cooperative learning model type Student Teams Achievement Division and Talking Stick included in the medium category, 2) There was no difference in increasing mathematical reasoning ability between students who obtained learning with the Student model Teams Achievement Division and students who obtain learning with the Talking Stick model.